Teologi kerja sebagai perspektif analitis terhadap hubungan stress kerja, kesejahteraan sekolah, dan performa kerja guru Kristen pendidikan anak usia dini: Studi kasus di Tapanuli Utara - May Rauli Simamora; Winarti Agustina; Marina Letara Nababan; Rosalina Apriliani Lumbantobing; Samuel Perdana Lumban Gaol (KURIOS, 2025)
Christian early childhood teachers hold a dual role, providing both academic and spiritual education in accordance with Christian teachings. This study examines the correlation between school well-being and work stress and their effects on the work performance of Christian PAUD/TK teachers in North Tapanuli, North Sumatra, using a quantitative correlational approach involving 106 teachers. The analysis reveals that school well-being, even with stress, is significantly correlated with teachers' work performance. These findings are then interpreted through the lens of a theology of work, which positions work as a divine calling. Improving work performance can be achieved by strengthening the dimensions of loving, having, being, and health within school well-being; managing stress through rest, prayer, reflection, and counseling support; and cultivating perseverance, resilience in the face of suffering, and relationships characterized by compassion and honesty in the workplace. Practical implications include policy recommendations to enhance school well-being, effective stress management strategies, and the strengthening of school principals' roles as servants of teacher welfare.   Abstrak Guru Kristen anak usia dini memiliki peran ganda dalam memberikan pendidikan akademik sekaligus pendidikan moral dan spiritual sesuai ajaran Kristen. Penelitian ini mengkaji korelasi antara kesejahteraan sekolah dan stres kerja terhadap performa kerja guru Kristen PAUD/TK di Tapanuli Utara, Sumatera Utara, menggunakan pendekatan kuantitatif korelasional dengan melibatkan 106 guru. Hasil analisis menunjukkan bahwa kesejahteraan sekolah dan stres kerja berkorelasi signifikan dengan performa kerja guru. Temuan ini kemudian dikaji melalui perspektif teologi kerja yang menempatkan kerja sebagai panggilan ilahi. Peningkatan performa kerja dapat diwujudkan melalui penguatan dimensi loving, having, being, dan health dalam kesejahteraan sekolah; pengelolaan stres berbasis istirahat, doa, refleksi, dan bantuan konselor; serta pembentukan karakter ketekunan, ketahanan dalam penderitaan, dan relasi yang penuh kasih sayang dan kejujuran di tempat kerja. Implikasi praktis mencakup rekomendasi kebijakan peningkatan kesejahteraan sekolah, strategi manajemen stres, dan penguatan peran kepala sekolah sebagai pelayan bagi kesejahteraan guru.